Case report: Intracranial epidermoid cyst in a cat - Terao, Masashi; Uemura, Takashi; Hasegawa, Hiroki; Ashida, China; Ehara, Ikuya; Ozawa, Tsuyoshi; Kamishina, Hiroaki (Frontiers in Veterinary Science, 2024)
A 9-year-old American Shorthair, castrated male, weighing 4.3 kg was presented to our hospital because of intermittent ataxia and tetraparesis for 6 weeks. On presentation, the cat was in a stupor and on recumbency, and had vertical nystagmus in both eyes. These clinical signs suggested a brainstem disorder. MRI showed a mass lesion in the caudal aspect of the fourth ventricle with hyperintensity on T2-weighted and FLAIR imaging, low-intensity on T1-weighted imaging, and enhanced margins on post-contrast T1-weighted imaging. The mass compressed the fourth ventricle, causing obstructive hydrocephalus. A second cystic lesion was found rostral to the cerebellum. After MRI, the cat experienced respiratory difficulties and the mass was removed by emergency craniectomy. Although the mass including the cyst wall was successfully removed, the cat was euthanized because spontaneous breathing did not return. The mass was histopathologically diagnosed as epidermoid cyst. A biopsy to the rostral cystic lesion had not been performed and therefore the etiology of this lesion remained unclear. This is the first case of feline intracranial epidermoid cyst in which MRI and surgical excision were performed. MRI findings were similar to those in humans and dogs, suggesting that imaging studies are useful in cats for the diagnosis of intercranial epidermoid cyst.